The role of dependence relationships in the value capture process - Bowman, Cliff (Academy of Management, 2022)
We view the firm as a complex system and deploy Emerson’s power dependence theory to explain who captures value in deals between the firm and its suppliers and customers. The value realised in a deal is the difference between the buyer and seller reservation prices and dependence is a function of need strength and the availability of alternative deals. We argue that prices are the outcome of perceived dependence relationships between buyer and seller. Dependence on the focal deal is based on the buyer or seller’s subjective judgements concerning the use value being traded, the other party’s dependence and the availability of alternative deals. We develop eight value levers which firms can deploy to improve their dependence relationships. We then use this value capture perspective to address three questions: 1) should firms pursue generic strategies? 2) what is a valuable resource? 3) how should firms approach strategic change? We conclude that any change or resource which enhances the firm’s dependence relationships improves firm performance.
Keywords: Value capture; dependence